THE EFFECT OF MULTICULTURAL APPROACH ON READING AND WRITING FOR ELEMENTARY STUDENT - Nashrullah, Nashrullah (Tadulako Social Science and Humaniora Journal, 2021)
This study aimed at investigating the effect of multicultural approach on reading comprehension and writing skills of grade V elementary school students in the South of Borneo. This is a quasi experimental research with nonequivalent-groups pretest and postest design. The participants experimental class was student of class VB MI Al-hamid Banjarmasin (n=38) and control class was students of class VA MI Al-Hamid Banjarmasin (n=36). Using reading comprehension and narrative writing test scores of students, multicultural approach questionnaire, and teaching assignment. This study reveals that multicultural approach affects reading comprehension and writing achievement and also becomes the best predictor of their experience and cultural knowledge, such as develops multiple perspectives, cultural counsciousness, increases intercultural competence, combats racism, sexiesm, prejudice, discrimination, and develops social action skills. Furthermore, multicultural approach has a significant effect and better than conventional teaching on students’ reading comprehension skills, and on writing skills are also better than convensional approach of teaching. As conclusion, multicultural approach can be considered as a teaching method in improving students’ reading comprehension and writing skills, from producing main idea and topik sentence, also writing non fiction text based on multicultural knowledge, awareness, skills and action. The research findings imply that teachers need to change their teaching model into multicultural approach and identify multicultural material to encourage students to do and bring up reading and writing activities related to tolerance.